Line Today’s Role in Meeting Young Adults’ News Needs (A Case Study on Communication Science Faculty’s Student) - Limilia, P; ., Rachmaniar (KnE Social Sciences, 2018)
In Indonesia, young adults are known to be the active users of social media. As digital natives, adolescents are accustomed to using social media for various reasons. Several researches clarify that the main reason behind young adults’ social media usage is to communicate with each other. However, today there is a shift in social media usage. Young adults use social media not only to communicate but also to find information, especially news. Hence, a social media platform today provides multiple features. It has now converted to a complete application that has many features, so that one need not use another application. One such example is Line application. Line application has many features such as messaging, games, decor, translation, stickers, and news. These features can be accessed through the main application. Consequently, young adults need not access news sites or newspapers in order to get the latest news. This study aims to explore Line Today’s role in meeting young adults’ news needs. Authors use quantitative methods with correlational as research design. Authors use questionnaire to get data from sample chosen by probability sampling. Research results reveal that Line Today has a significant role in meeting young adults’ news needs, as it provides several news that are suitable for college students and those that meet their need. Keywords: social media, line, college students, needs, news